Cytotoxic and Antioxidant Properties of Natural Bioactive Monoterpenes Nerol, Estragole, and 3, 7-Dimethyl-1-Octanol. (23rd November 2022) - Coêlho, Mayara Ladeira; Islam, Muhammad Torequl; Laylson da Silva Oliveira, George; Oliveira Barros de Alencar, Marcus Vinicius; Victor de Oliveira Santos, José; Campinho dos Reis, Antonielly; Oliveira Ferreira da Mata, Ana Maria; Correia Jardim Paz, Márcia Fernanda; Docea, Anca Oana; Calina, Daniela; Sharifi-Rad, Javad; Amélia de Carvalho Melo-Cavalcante, Ana
Abstract : The therapeutic potential of medicinal plants is noted because of the presence of varieties of biochemicals. The monoterpenes, like nerol, estragole, and 3, 7-dimethyl-1-octanol, have been reported for antimicrobial, antifungal, anthelmintic, and antioxidant activities. This study evaluated the toxic, cytotoxic, and oxidant/antioxidant effects of these compounds by several in vitro (DPPH and ABTS radical scavenging, and ferric reducing potential), ex vivo (hemolysis), and in vivo ( Artemia Salina and Saccharomyces cerevisiae ) assays. Results suggest that estragole and 3, 7-dimethyl-1-octanol at 31.25–500 μ g/mL did not exhibit significant cytotoxic effects in the A. Salina and hemolysis tests. Nerol showed significant cytotoxic effects on these test systems at all test concentrations. The monoterpenes showed radical (ABTS + and DPPH ) scavenging capacities in a concentration-dependent manner in vitro tests. However, they did not oxidize the genetic material of S. cerevisiae (SODWT, Sod1Δ, Sod2Δ, Sod1/Sod2Δ, Cat1Δ, and Cat1Δ/Sod1Δ) lines. Among the three monoterpenes, nerol may be a good candidate for antioxidant and anti-tumor therapies.